PENGARUH MODEL PEMBELAJARAN ACTIVE DEBATE TERHADAP KETERAMPILAN BERBICARA SISWA KELAS V SDN 15 MATARAM - Fitratunnisah Fitratunnisah; Ida Bagus Kade Gunayasa; Moh. Irawan Zain (JURNAL ILMIAH PENDAS: PRIMARY EDUCATION JOURNAL, 2022)
This research aims to find out the effect of Active Debate Learning Model on The Speaking Skills of Students of Class V SDN 15 Mataram. The type of research used is Quasi Eksperimental Design type Nonequivalent Control Group Design. The sampling method used is purposive sampling. The population in this study was 41 students. The data collection methods used are tests and observations. The normality test is carried out by calculating data in the form of pre-test speaking skills and post-test using the formula kolmogrov smirnov with a level of sig 5% (0.05) then after the normal distribution data is carried out homogeneity test obtained from the results of post-test calculations, The hypothesis test is then carried out using the calculation of student post-test data. The results of the data analysis obtained a sig 2 tailed value of 0.016 which is less than 0.05, then based on the research hypothesis, if the sig 2 tailed value ≤ 0.05 t-table then Ho is rejected and Hₐ accepted. This shows that there is an influence of active debate learning model on the speaking skills of students of Class V SDN 15 Mataram Year of Study 2021. With this research is expected to be used as a reference reference for further research, on different subjects.